Analisis Hiyal Dalam Produk Deposit Berasaskan Kontrak Tawarruq di Perbankan Islam Malaysia: Hiyal Analysis in Deposit Product based on Tawarruq Contract in Malaysian Islamic Banking - Zulkepli, Muhammad Izzul Syahmi; Mohamad, Mohammad Taqiuddin (Online Journal of Research in Islamic Studies, 2019)
Hiyal is defined as the ability of someone to seek solution to some difficulties and to achieve certain goals. Currently, hiyal is applied widely especially in muamalat activity related to Syariah law. For example, in offering Islamic banking product, tawarruq contract that is claimed as one form of hiyal is applied in Islamic banking product. However, the use of tawaruq contract is still debated among Muslim scholars. The difference is clearly seen through reolution issued by organization related to Islamic finance. For instance, the organization Majma’ al-Fiqh al-Islami does not allow tawarruq al-munazzam contract to be applied in banking product, meanwhile Accounting and Auditing Organisation for Islamic Finance Institutions (AAOIFI) allow it. Therefore, this study analyse the elements of hiyal contained in deposit products based on tawarruq in Islamic banking. To achieve the objective, researchers utilised the library research by referring to related literature. The qualitative data were subsequently analyse using content analysis method descriptively. Research finding implies that there are several Syariah issues concerning hiyal in pre-arrangement practice, dual-agency, commodities and customer deposit holding by Islamic banking institutions before tawarruq transaction is done. Hence, industry player in the Islamic Banking sector should direct the attention to these issues in order to preserve the reputation of Syariah-based banking.